Hydralazine-Induced ANCA Vasculitis Presenting With Pericarditis: A Novel Case and Literature Review - Ahmed Sami Hammami; Osejie Oriaifo; Sinda Hidri; Sukhvir Singh; Husam El Sharu; Joshua Peltz; Soroush Nomigolzar; Kunjan Udani (Case Reports in Cardiology)
Hydralazine, a commonly used arterial vasodilator for managing congestive heart failure and hypertension, is known to be associated with drug-induced lupus and, less frequently, antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV). Drug-induced AAV typically carries a favorable long-term prognosis and is not commonly linked to cardiovascular or ocular involvement. Pericarditis cases associated with hydralazine have not been previously reported. We present a rare case involving an 85-year-old woman on long-term hydralazine therapy, initially presenting with acute lobar pneumonia. During her hospitalization, she developed pericarditis, chemosis, and conjunctivitis in her eyes, along with cutaneous lesions described as a maculopapular rash on her face, tender bullae on her digits, and a petechial rash on her back. Laboratory findings were consistent with drug-induced AAV, showing positive myeloperoxidase and proteinase 3 antibodies. An attempted diagnostic pericardiocentesis was unsuccessful. Hydralazine was discontinued, and she was successfully treated with corticosteroids and tolerated immunosuppression well. Subsequently, she recovered and was discharged from the hospital.